Student Motivation in Biology Learning Using Augmented Reality and Comics - Damopolii, Insar (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2025)
Background: This study aims to analyze students' learning motivation while they are involved in biology learning using comics and AR, taking into account gender factors. Method: Researchers conducted a survey of 86 high school students. Motivation was measured using a questionnaire based on the ARCS model. Learning motivation was analyzed based on the total motivation score, and the average for its four indicators, then a test for differences based on gender was conducted. Results: In biology learning using comics and AR, high learning motivation dominated. The total score of students' learning motivation was high (76.19), and the satisfaction indicator with an acquisition of 85.66 (very high). Meanwhile, confidence, relevance, and attention indicators showed a high level with an average of 72.04, 79.47, and 74.9, respectively. The learning motivation of male and female students showed a significant difference (Sig. = 0.043 < 0.05). Based on the indicators, the difference was only shown in the attention indicator (Sig. < 0.05). Conclusion: Biology learning motivation during student involvement in learning using comics and AR is in the high category. Significant differences in male and female students are related to the total score of motivation and the attention indicator, while others do not show any differences in both genders. Keywords : Cartoon, learning satisfaction, motivation to learn, biology learning